Newly Proposed Sepsis-Induced Coagulopathy Precedes International Society on Thrombosis and Haemostasis Overt-Disseminated Intravascular Coagulation and Predicts High Mortality. (July 2020) - Iba, Toshiaki; Arakawa, Makoto; Di Nisio, Marcello; Gando, Satoshi; Anan, Hideaki; Sato, Koichi; Ueki, Yutaka; Levy, Jerrold H.; Thachil, Jecko
Background: Disseminated intravascular coagulation (DIC) has been recognized as an urgent and critical condition in patients with sepsis. Therefore, unfamiliar and time-consuming tests or a complex scoring system are not suitable for diagnosis. Sepsis-induced coagulopathy (SIC), a newly proposed category delineated by a few global coagulation tests, has been established as an early warning sign for DIC. The purpose of this study was to elucidate the characteristics of SIC, especially in relation to the score of the International Society on Thrombosis and Haemostasis (ISTH) for overt DIC. Method: A data set for 332 patients with sepsis who were suspected to have DIC, antithrombin activity <70%, and treated with antithrombin substitution was utilized to examine the relationship between SIC and overt DIC. The performance of SIC calculated at baseline (ie, before treatment) as well as on days 2, 4, or 7 was analyzed in terms of its ability to predict 28-day mortality and overt DIC. Results: At baseline, 149 (98.7%) of 151 patients with overt DIC according to the ISTH definition were diagnosed as having SIC. Of the 49, 46 (93.9%) patients who developed overt DIC between days 2 and 4 had received a prior diagnosis of SIC. The sensitivity of baseline SIC for the prediction of death was significantly higher than that of overt DIC (86.8% vs 64.5%, P < .001). The sensitivity of SIC on days 2, 4, and 7 was significantly higher than those of overt DIC (96.1%, 92.3%, and 84.4% vs 67.1%, 57.7%, and 50.0%, P < .001, .001, and .001, respectively), although the specificity of SIC was lower at all time points.